Portfolio diversification benefits of Malaysia's stock indices with commodities : an analysis based on the MGARCH-DCC and wavelet techniques - Ahmad Monir Abdullah; Hishamuddin Abdul Wahab; Mohd Fahmi Ghazali; Hazriah Hasan; Rafiatul Adlin Mohd Ruslan; Wan Muhd Nasrul Hadi Wan Abdul Aziz (Penerbit Universiti Kebangsaan Malaysia, 2022)
This research examined the potential for diversifying Malaysian Islamic and conventional stock indexes with other commodities, such as crude oil, Bitcoin, and gold, with time-varying differences or investors' varied investment horizons, which researchers had previously overlooked. Methods like the Multivariate GARCH-Dynamic Conditional Correlation (MGARCH-DCC) and the continuous wavelet transformation (CWT) were employed since they are time-varying and time scale-dependent. Crude oil, Bitcoin, and gold are shown to be leading the stock indices in our vector error correction model (VECM) analysis, implying that changes in the price of these commodities influence the stock indices. The findings also indicate that investors exposed to Malaysian stock indexes and investing in Bitcoin may benefit from significant diversification advantages across almost all investment horizons. However, the MGARCH-DCC result shows that Bitcoin is highly unpredictable. As a precaution, Malaysian investors should choose gold as a diversification instrument which is more stable. The wavelet model demonstrates that investors in Malaysia’s Islamic and conventional indices may benefit from the gold holding for durations ranging from 1 to 64 days and 128 days beyond. The findings highlight the importance of using contemporary techniques to identify diversification opportunities for investors with varied investment horizons or holding stocks for various times.